O potrzebie utrzymania przepisu art. 256 § 3 k.k. - Lachowski, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This study concerns the issue of exclusion of criminal responsibility for an offence under Article 256 § 2 of the Penal Code. The article analyses the prerequisites for the application of the justification normalized in Article 256 § 3 of the Penal Code. Critical assessments of this provision in the criminal law literature and calls for its repeal are also presented. The main reservation is related to the fact that it is not possible to commit an offence under Article 256 § 2 of the Penal Code within the framework of artistic, educational, collecting or scientific activities, because the perpetrator in such a case does not act with the aim of disseminating prohibited content, and above all does not propagate totalitarian systems. In this situation, the provision of Article 256 § 3 of the Penal Code appears to be unnecessary. However, the author of this study has attempted to demonstrate if an offence can be construed as a component of such types of activity, it falls under Article 256 § 2 of the Penal Code. This leads to the conclusion that the regulation contained in Article 256 § 3 of the Penal Code is needed in the Polish legal order.
Keywords: ustroje totalitarne; nawoływanie do nienawiści; ideologia; działalność artystyczna; działalność naukowa; działalność edukacyjna; działalność kolekcjonerska; wyłączenie odpowiedzialności karnej